Implementation of the BIM Methodology for the diagnosis and pathology activities of construction in CEMOSA. - Troyano-Moreno, Miguel; Jiménez Redondo, Noemí; García Villena, Francisco Antonio; Hernández Villalobos, Eusebio; Sevilla-Hurtado, Lorenzo (My University, 2024)
The BIM methodology has been established as the most efficient way to design, build and operate a certain asset in the AEC-FM industry (Architecture, Engineering, Construction, and Facility Management). However, there are still activities within this industry where their implementation is not sufficiently mature, as occurs in diagnosis and pathology studies, due to the lack of a standard to store damage information and the lack of computer applications to properly generate the corresponding information models. This communication describes the developments carried out by the company CEMOSA to address these activities through the BIM methodology, focusing on the description of the processes, data models and the functionality of the applications that allow collect information and generate information models.
Keywords: Ingeniería - Metodología; Inspection; Damage; Building Information Modeling (BIM); Damage Information Modeling (DIM); Industry Foundation Classes (IFC)